Evidences of safety and tolerability of the zoledronic acid 5 mg yearly in the post-menopausal osteoporosis: the HORIZON project - F. Bertoldo; L. Dalle Carbonare; V. Lo Cascio (PAGEPress Publications, 2011)
Bisphosphonates are the most commonly prescribed medications for the treatment of osteoporosis. Despite evidence supporting the anti-fracture efficacy of aminobisphosphonates approximately 50% of patients do not follow their prescribed treatment regimen and/or discontinue treatment within the first year. Poor compliance is associated with negative outcomes, including increased fracture risk. Tolerability and safety are among the causes of poor compliance. Intravenous bisphosphonates avoids the gastrointestinal intolerance and the complex dosing instruction of the oral route ensuring full compliance which may provide improved efficacy. However, there are some concerns regarding potent intravenous bisphosphonates as zoledronic acid with respect to tolerability, mainly the acute phase response and to safety, mainly a theoretical risk of over suppression of bone turnover, renal toxicity and osteonecrosis of the jaw. In the HORIZON study, 152 patients on active treatment (82) or placebo (70) underwent to a bone biopsy after double tetracycline labeling. Bone biopsies (iliac crest) were obtained at the final visit at month 36, 1 year after the last infusion. The biopsies were analyzed by histomorphometry on bone sections and by micro-CT (μCT) analysis. 143 biopsies (76 zoledronic acid, 67 placebo) had at least one μCT parameter measured and 111 were available for quantitative histomorphometry (59 zoledronic acid, 52 placebo). Micro-CT analysis of bone structure revealed higher trabecular bone volume (BV/TV), decreased trabecular separation (Tb.Sp), and a strong trend towards improvement in connectivity density in biopsies obtained from patients treated with zoledronic acid, indicating preservation of trabecular bone structure with respect to placebo. Histomorphometric analysis obtained from patients treated with zoledronic acid exhibited reduction of bone turnover, as suggested by decreased activation frequency (Ac.F) by 63%, mineralizing surface (MS/BS), bone formation rate (BFR/BV). In addition, mineral appositional rate (MAR), reflecting the bone-forming capacity of osteoblastic teams at the bone multicellular unit (BMU) level, was significantly higher in patients on active treatment. No sign of excessive suppression of bone turnover or mineralization impairment was detected, confirming the safety of the treatment with intravenous zoledronic acid once a year. These interesting findings are discussed in the article, particularly in terms of new histomorphometric results and clinical findings supporting the tolerability and safety of zoledronic acid.